Structured biodegradable microparticles produced using glass microfluidic flow focussing devices - Ekanem Ekanem; Goran Vladisavljevic (2014)
Herein is reported the production of biodegradable poly (lactic acid) (PLA) and poly (lactic-co-glycolic acid) (PLGA) particles having modifiable internal and surface microstructures via single step emulsification using microfabricated 3D (axisymmetric) flow focusing glass capillary microfluidic devices and subsequent solvent evaporation. Controlled production of emulsion droplets was achieved and the morphology of particles produced after evaporation was investigated to ascertain its effect on hydrophobic drug encapsulation and release.